Mathematical modeling of fluid movement inside the eyeball during intravitreal injection - D. V. Lipatov; S. A. Skladchikov; N. P. Savenkova; V. V. Novoderezkin; Ph. I. Vysikailo (Российский офтальмологический журнал, 2022)
Intravitreal injections show an avalanche-like growth the world over.   Purposes: 1) create a mathematical model of the eyeball and fluid movement inside the eye, assuming the simplified structure of the vitreous body (without tanks); 2) estimate the time span when the drug substance remains in the cavity of the vitreous body until it is completely washed out, depending on the injection site; 3) observe and evaluate the path of drug movement in the vitreous body cavity; 4) evaluate the variation of time when the drug is located in the vitreous body cavity, depending on the presence or absence of complete detachment of the vitreous body.   Results. If the drug is injected closer to the center of the eyeball, the time when it is located in the vitreous is increased as compared to parietal injection. With full vitreous body detachment, the location time of the drug increases as compared to its normal location, which favorably affects the prolongation of the therapeutic effect.   Conclusion. As this is a pilot study, many parameters are approximate, so the results obtained cannot be mechanically extrapolated to the live human eye subjected to intravitreal injections, due to the complexity of the processes occurring in eyeball.